NSRG-01. PRIMARY GLIOBLASTOMA IN THE PINEAL REGION OF A PEDIATRIC PATIENT: A CASE REPORT AND REVIEW OF THE LITERATURE. Issue 2 (22nd June 2018) - Hwang, Lee; Yeaney, Gabrielle; Tekautz, Tanya; Onwuzulike, Kaine; Recinos, Violette
Abstract: Glioblastoma, a very aggressive type of astrocytoma (WHO grade IV), is extremely rare in the pineal region particularly in the pediatric population. With only 5 pediatric cases reported since 1972, we present another report in the setting of technological advances in neurosurgical intervention. As in this case, patients usually present with non-specific symptoms such as headache, nausea, visual changes, and altered mental status. A complete evaluation includes an MRI of the entire neuro-axis. Neurosurgical management of more acute concerns related to increased intracranial pressure can initially consist of a less invasive endoscopic third ventriculostomy (ETV), even if a more invasive microsurgical resection is ultimately required. Furthermore, thorough molecular and histological analyses can guide postoperative adjuvant therapies. Unfortunately, the overall prognosis of a patient with pineal glioblastoma is poor. Despite aggressive treatment with surgery and adjuvant therapies, the average survival rate is less than one year after diagnosis. The potential benefits and risks of a lengthy and complex microsurgical resection of a pineal glioblastoma must be extensively discussed with patients and/or their families. Moreover, due to the aggressive nature of glioblastomas, these patients must be closely monitored postoperatively for progression or recurrence. Though extremely rare, pineal glioblastomas are amenable to neurosurgical intervention for CSF diversion, both ETV and shunt, as well as microsurgical resection. Furthermore, as with any pediatric case, involvement of the patient's family, pediatrician, and oncologist is crucial in providing comprehensive and long-term supportive care.